A Case of Aspergilloma with Mucin Secreting Adenocarcinoma in the Cavity Wall (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
A Pulmonary aspergillosis and lung cancer rarely occur simultaenously. We report a 63 year old female with complaint of heamoptysis. Contrast enhanced chest revealed a cavity containing fungus ball in the left lung lower lobe suggestive of a fungoma. Left lower lobectomy was done for intractable heamoptysis. The histological examination of the reselected specimen showed colonies of aspergilli in the cavity and mucin secreting adenocarcinoma in the cavitary wall. Careful gross examination of the patient must be done to rule out metastasis.SAARC J TUBER LUNG DIS HIV/AIDS, 2015; 12(1), Page: 39-41